2015
DOI: 10.1155/2015/638025
|View full text |Cite
|
Sign up to set email alerts
|

Massive Neurilemoma of the Hard Plate in Which Preoperative Diagnosis Was Difficult

Abstract: The patient was an 84-year-old man who was referred to our hospital in mid-December 2012 for a close examination of a mass arising from the left side of the hard palate that was found by a local dentist. The initial examination revealed the presence of a 3.0-cm elastic soft, dome-shaped mass in the left hard palate. CE-CT showed a lesion of size 1.8 × 1.4 cm in the right hard palate, which extended upward and invaded the nasal cavity. The mass was a solid tumor associated with resorption of surrounding bone an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Clinically, most of the lesions were reported as nontender and/or firm/hard. Tenderness was elicited only twice 21 37 , while soft swelling on palpation was reported in four cases 18 38 43 44 . Jones et al reported a cystic component in the lesion.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Clinically, most of the lesions were reported as nontender and/or firm/hard. Tenderness was elicited only twice 21 37 , while soft swelling on palpation was reported in four cases 18 38 43 44 . Jones et al reported a cystic component in the lesion.…”
Section: Resultsmentioning
confidence: 97%
“…15 16 33 37 38 51 The lesion was seen eroding into the right maxillary sinus through the floor of the sinus in one case; 15 while in another patient, the mass was seen invading the nasal cavity through the palatal bone. 38 Orthopantomogramand maxillary occlusal radiography showed mostly a radiolucent lesion, without any bony alteration or periapical changes. In MRI exams, the mass appeared hypo-to-isointense on T1-weighted images and hyperintense on T2-weighted images, in almost all of the cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations